Anti-growth effect of a novel trans-dichloridobis[2-(2-hydroxyethyl)pyridine]platinum (II) complex via induction of apoptosis on breast cancer cell lines. Issue 15 (1st August 2015) - Oral, Arzu Yilmaztepe; Cevatemre, Buse; Sarimahmut, Mehmet; Icsel, Ceyda; Yilmaz, Veysel Turan; Ulukaya, Engin
Graphical abstract: Abstract: Breast cancer still continues to be the leading cause of cancer-related mortality in women worldwide. Although advances have been made in the treatment of this disease during the past decade, new approaches and novel compounds are urgently needed. The aim of this study was to evaluate the cytotoxic activity of trans -[PtCl2 (2-hepy)2 ] [2-hepy=2-(2-hydroxyethyl) pyridine] on breast cancer cell lines, MCF-7 and MDA-MB-231. The platinum (II) complex was synthesized and characterized by our laboratory working group. Anti-growth effect was assayed by the MTT and ATP viability assays and also monitored real-time using xCELLigence system. The mode of cell death was evaluated by using the fluorescence microscopy (Hoechst 33342 + Calcein-AM + Propidium iodide staining), Western blotting (cleaved PARP and caspase 3, total caspase 8), flow cytometry (quantitative analysis of live, early/late apoptotic, dead cells and caspase 3/7 activity) and the RT-PCR (the genes analyzed were BCL-2L10, BIK, BAX, BCL-2, FASLG, HRK, TNFRSF10B, and TNFRSF10A). The platinum (II) complex had anti-growth effect in a dose dependent manner in vitro. Cells were killed by apoptosis as evidenced by the pyknotic nuclei, cleavage of poly-(ADP-ribose) polymerase (PARP) and induction of active caspase-3. These results suggest that the complex might represent a potentially active novel drug for the breast cancer treatment and warrants further studies due to its promising cytotoxic activity.